Osteopetrosis in a Patient of Systemic Sclerosis Sine Scleroderma: A Rare Association - Pati, Saroj K.; Raja, Praveen; Behera, Ajoy K.; Ranganath, T.G.; Bodhey, Narendra K. (Indian Journal of Radiology and Imaging, 2021)
Systemic sclerosis is a connective tissue disorder of unknown etiology. Although it is a multisystemic disorder, skin thickening is considered as a hallmark of the disease. It usually involves the lungs, gastrointestinal, and musculoskeletal systems. However, a rare subset of systemic sclerosis, systemic sclerosis sine scleroderma, is characterized by internal organ involvement and positive serologic markers with the total or partial absence of cutaneous manifestations. We present a rare association of osteopetrosis in a case of systemic sclerosis sine scleroderma, in a 22-year-old male patient, who presented with pulmonary symptoms as his chief complaints, unreported so far in literature.
Keywords: interstitial lung disease; osteopetrosis; rugger jersey spine; systemic sclerosis sine scleroderma